1984
DOI: 10.1038/309356a0
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of myelin basic protein-sensitized T cells produces chronic relapsing demyelinating disease in mice

Abstract: The autoimmune disease of the central nervous system (CNS), experimental allergic encephalomyelitis (EAE), is induced by challenge of genetically susceptible animals with spinal cord homogenates or myelin basic protein (MBP). Chronic and relapsing forms of the disease have some similarities to human demyelinating disorders, namely, multiple sclerosis, and are of particular interest. EAE can be transferred passively with sensitized lymphoid cells into syngeneic animals but transferred EAE has been believed to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(108 citation statements)
references
References 21 publications
0
107
0
1
Order By: Relevance
“…EAE is induced by immunizing susceptible animals with myelin-derived proteins (or peptides) such as proteolipid protein (PLP), myelin oligodendrocyte glycoprotein (MOG) or myelin basic protein (MBP). Animals with EAE reproduce the major clinical and histopathological features of MS and it has been demonstrated that EAE can be transferred adoptively in healthy animals by injecting myelin-specific CD4 + T cells (32)(33)(34). Taking into account the data gathered over the years, it is believed that a complex combination of genetic and environmental factors induces the activation of myelin-specific peripheral T cells in MS patients.…”
Section: Ms Pathogenesismentioning
confidence: 99%
“…EAE is induced by immunizing susceptible animals with myelin-derived proteins (or peptides) such as proteolipid protein (PLP), myelin oligodendrocyte glycoprotein (MOG) or myelin basic protein (MBP). Animals with EAE reproduce the major clinical and histopathological features of MS and it has been demonstrated that EAE can be transferred adoptively in healthy animals by injecting myelin-specific CD4 + T cells (32)(33)(34). Taking into account the data gathered over the years, it is believed that a complex combination of genetic and environmental factors induces the activation of myelin-specific peripheral T cells in MS patients.…”
Section: Ms Pathogenesismentioning
confidence: 99%
“…Discussion with mouse tEAE models was not included as they result in inflammation which progresses to demyelination (Mokhtarian et al, 1984) while the MBP-specific T lymphoblasts induced tEAE in the Lewis rat is monophasic with full recovery (Holda et al, 1980;Paterson et al, 1981).…”
Section: Autoradiography and Immunochemistry Correlation With The Uprmentioning
confidence: 99%
“…Because of similarities in clinical symptoms and CNS histology, [1][2][3][4][5] EAE serves as a model for multiple sclerosis and can be induced in mice by either immunization with myelin protein or peptides 6 or by adoptive transfer of myelin-specific Th1 CD4 ϩ T cells. 7,8 As a result, inflammatory cells consisting mostly of CD4 ϩ T lymphocytes and macrophages infiltrate the CNS leading to demyelination and neuronal damage. 9 Tumor necrosis factor receptor 1 (TNFR1), also known as the p55 kd TNF receptor, binds to two ligands, TNF and lymphotoxin-␣.…”
mentioning
confidence: 99%